Hubungan Dukungan Keluarga dengan Harga Diri Mantan Pecandu Narkoba Di BNN Sumatera Utara - Ayu Surgana; Eryanti Novita (Tabularasa: Jurnal Ilmiah Magister Psikologi, 2023)
This study aims to determine and empirically test the relationship between family support and self-esteem of former drug addicts at BNN North Sumatra. The population in this study were drug addicts at the BNN North Sumatra as many as 80 people. The sampling technique in this study used total sampling. Self-esteem compiled by researchers based on aspects according to Coopersmith (in Komaruddin et al, 2016) Power (power), Significance (Significance), Virtue (Virtue), Ability (Competence). Family support in this study was measured by aspects according to Gunarsa Gunarsa (2012): Giving real support, giving attention, giving warmth, and giving love and protection. It is known that there is a positive relationship between family support and self-esteem. This result is evidenced by the correlation rxy = 0.979, with significant p = 0.000 0.05. The determinant coefficient (r2) of the relationship between the independent variable and the dependent variable is r2= 0.959. This shows that family support is distributed 95.90% of self-esteem. It can be concluded that family support is very low with a hypothetical mean of 67,500 and an empirical mean of 52,600. Furthermore, self-esteem is classified as very low with a hypothetical mean value of 112,500 and an empirical mean of 87,750.